Localized and Controlled Delivery of Nitric Oxide to the Conventional Outflow Pathway via Enzyme Biocatalysis: Toward Therapy for Glaucoma. Issue 16 (21st February 2017) - Chandrawati, Rona; Chang, Jason Y. H.; Reina‐Torres, Ester; Jumeaux, Coline; Sherwood, Joseph M.; Stamer, W. Daniel; Zelikin, Alexander N.; Overby, Darryl R.; Stevens, Molly M.
Abstract : Nitric oxide (NO) is able to lower intraocular pressure (IOP); however, its therapeutic effects on outflow physiology are location‐ and dose‐dependent. A NO delivery platform that directly targets the resistance‐generating region of the conventional outflow pathway and locally liberates a controlled dose of NO is reported. An increase in outflow facility (decrease in IOP) is demonstrated in a mouse model.